COMPUTED TOMOGRAPHY AND GROSS ANATOMICAL STUDIES ON THE TEMPOROMANDIBULAR AND SUPRAORBITAL REGIONS OF ONE-HUMPED CAMEL (CAMELUS DROMEDARIUS) - Mohamed Marzok; Khalid M. Alkhodair; Mohamed Nazih; Mohamed W. El-Sherif (Slovenian Veterinary Research)
Objective: The objective of this study was to investigate the detailed surgical anatomy of the temporomandibular and supraorbital regions in camels using anatomical dissection and computed tomography (CT) scanning. The study aimed to provide precise anatomical descriptions and assess the feasibility of surgical interventions within the orbital cavity via the orbital fossa.